The World of the Old Testament : the people and places of the ancient Near East - Arnold, Bill T., ed.; Strawn, Brent A., ed. (Grand Rapids, Michigan : Baker Academic, 2016)
Leading experts introduce the people and contexts of the Old Testament. What people groups interacted with ancient Israel? Who were the Hurrians and why do they matter? What do we know about the Philistines, the Egyptians, the Amorites, the Assyrians, the Babylonians, and others? In this up-to-date volume, leading experts introduce the peoples and places of the world around the Old Testament, providing students with a fresh exploration of the ancient Near East. The contributors offer comprehensive orientations to the main cultures and people groups that surrounded ancient Israel in the wider ancient Near East, including not only Mesopotamia and the northern Levant but also Egypt, Arabia, and Greece. They also explore the contributions of each people group or culture to our understanding of the Hebrew Scriptures. This supplementary text is organized by geographic region, making it especially suitable for the classroom and useful in a variety of Old Testament courses. Approximately eighty-five illustrative items are included throughout the book. - Publisher.
Greece and the Greeks / Walter Burkert.
Includes bibliographical references and index.
Keywords: Bible. Old Testament -- History of contemporary events; Middle East -- History -- To 622; Middle East -- History, Local